2012
DOI: 10.1016/j.trstmh.2012.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological survey of the prevalence of intestinal parasites among schoolchildren in Sari, northern Iran

Abstract: Parasitic infection is highly prevalent throughout the developing countries of the world. Research on the prevalence of intestinal parasitic infections in various geographic regions is a prerequisite for the development of appropriate control strategies. A cross-sectional study was conducted to determine the prevalence of intestinal parasitic infections among schoolchildren in public primary and secondary schools in the urban areas of Sari, Mazandaran province, northern Iran. The study was conducted from Novem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
49
4
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(65 citation statements)
references
References 17 publications
11
49
4
1
Order By: Relevance
“…In the present study, the most common intestinal parasites were B. hominis and G lamblia,, which is similar to the results reported by Kia et al (2008) and Daryani et al (2012) in Mazandaran province [12,14]. B. hominis is the microscopic parasitic organism found throughout the world [20].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In the present study, the most common intestinal parasites were B. hominis and G lamblia,, which is similar to the results reported by Kia et al (2008) and Daryani et al (2012) in Mazandaran province [12,14]. B. hominis is the microscopic parasitic organism found throughout the world [20].…”
Section: Discussionsupporting
confidence: 91%
“…The overall prevalence of parasites infection was 14.2% in the current study. In the previous studies conducted on specific community groups in Mazandaran province, the prevalence rates of IPIs were reported to be 15.5%, 26.2%, 33.3%, and 12% in the food handlers, mentally challenged children, school children, and rural inhabitants, respectively [11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was associated with diarrhea in the tropics and subtropics, since it was found in patients throughout the world. The reported prevalence rates of intestinal protozoa varied from 1.5% to 10% in developed countries, with much higher rates of 30%to 50% in developing countries [9,10].…”
mentioning
confidence: 99%
“…Sharif et al reported 26.2% infection of intestinal protozoans (19) and Daryani et al reported 33.3% infection rate (20) in the North of Iran and Assmar et al (1999) reported that the rate of parasitic infection in 6252 pupils in Mazandaran province was 57.1%, which may be associated with poor sanitation, low education and drinking water contamination (21)(22)(23). A recent study by Kousha et al (2011) in Tabriz, Northwest of Iran, reported 44% infection by one or more intestinal parasites in school children (18).…”
Section: Discussionmentioning
confidence: 99%